Carboxymethlyated cellulose nanofibrils(CMCNFs) embedded in polyurethane foam as a modular adsorbent of heavy metal ions. (1st September 2018) - Hong, Hye-Jin; Lim, Jin Seong; Hwang, Jun Yeon; Kim, Mikyung; Jeong, Hyeon Su; Park, Min Sang
Graphical abstract: Highlights: Carboxymethylated cellulose nanofibrils(CMCNFs) is promising metal bio-sorbent. Polyurethane(PU) is an appropriate support for sorbent due to macroporous structure. 3D network of CMCNFs via PU scaffold is prepared by an in-situ attachment process. CMCNFs/PU foam exhibits highly porous structure with improved mechanical property. CMCNFs/PU foam shows excellent heavy metal adsorption capacity and recyclability. Abstract: Polyurethane (PU) foam was utilized as an efficient and durable template to immobilize surface-functionalized nanocellulose, carboxymethylated cellulose nanofibrils (CMCNFs), to address some of the challenges for the application of nanocellulose to industrial water purification, such as its agglomeration, difficulties in separation from effluent, and regeneration. The composite foams exhibited well dispersed CMCNFs in PU matrices with open pore structure; the hydrogen bonds result in the enhancement of mechanical strength, which is another requirement of ideal adsorbents for wastewater treatment. The composite foams show high adsorption capacity and the potential for recyclability. The combination of optimal surface modification of nanocellulose with isolation and immobilization in durable PU foam achieved an efficient and cost-competitive bio-sorbent for heavy metal ions.